2015
DOI: 10.1021/acs.bioconjchem.5b00123
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Delivery of Highly Diverse Bioactive Compounds from Blend Electrospun Fibers for Skin Wound Healing

Abstract: Blend emulsion electrospinning is widely perceived to destroy the bioactivity of proteins, and a blend emulsion of water-soluble and nonsoluble molecules is believed to be thermodynamically unstable to electrospin smoothly. Here we demonstrate a method to retain the bioactivity of disparate fragile biomolecules when electrospun. Using bovine serum albumin as a carrier protein; water-soluble vitamin C, fat soluble vitamin D3, steroid hormone hydrocortisone, peptide hormone insulin, thyroid hormone triiodothyron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Their study used similar emulsion electrospinning parameters as in our study (10% aqueous phase, non-ionic surfactant), and the lack of bioactive protein detected from their emulsion electrospun fibers may be due to the differences in polymers and organic solvents used or the inherent instability of growth factor proteins, which have half-lives on the order of minutes (Tessmar and Göpferich, 2007). A study by Peh et al loaded multiple proteins into poly(lactic-co-glycolic acid) emulsion electrospun fibers with a 10% aqueous phase and found that the bioactivity recovered was highly dependent on the protein (Peh et al, 2015), as is supported by the results of our study. Finally, many studies incorporating proteins into electrospun fibers for wound healing and tissue engineering demonstrate function of the encapsulated proteins but bioactivity retention is not quantified due to the non-enzymatic nature of the protein investigated (Briggs et al, 2015; Choi et al, 2015; Hu et al, 2016; Li et al, 2010; Wang et al, 2015).…”
Section: Resultssupporting
confidence: 89%
“…Their study used similar emulsion electrospinning parameters as in our study (10% aqueous phase, non-ionic surfactant), and the lack of bioactive protein detected from their emulsion electrospun fibers may be due to the differences in polymers and organic solvents used or the inherent instability of growth factor proteins, which have half-lives on the order of minutes (Tessmar and Göpferich, 2007). A study by Peh et al loaded multiple proteins into poly(lactic-co-glycolic acid) emulsion electrospun fibers with a 10% aqueous phase and found that the bioactivity recovered was highly dependent on the protein (Peh et al, 2015), as is supported by the results of our study. Finally, many studies incorporating proteins into electrospun fibers for wound healing and tissue engineering demonstrate function of the encapsulated proteins but bioactivity retention is not quantified due to the non-enzymatic nature of the protein investigated (Briggs et al, 2015; Choi et al, 2015; Hu et al, 2016; Li et al, 2010; Wang et al, 2015).…”
Section: Resultssupporting
confidence: 89%
“…11 In skin substitutes, collagen is often applied in the form of a gel, 12,13 or it is used in composites with other natural or synthetic materials. 14,15 Previous studies have revealed that collagen supports wound healing. Niiyama and Kuroyanagi combined collagen with hyaluronic acid and functionalized this composite with EGF.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Peh et al impregnated a cocktail of compounds (Vitamin C, hydrocortisone, insulin, triiodothyronine, EGF, and Vitamin D3) into electrospun PLGA/collagen fiber mats and tested their potential utility in wound healing applications. These researchers also confirmed the bioactivity of the released molecules in vitro [171]. …”
Section: Areas Of Potential Clinical Use For the Topical Applicatimentioning
confidence: 62%